Réflexion sur la responsabilité sociale des entreprises multinationales extractives en droit international africain des droits de l’homme - Ipala Atangana, Vanessa (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2026)
La responsabilité sociale des entreprises multinationales extractives constitue une préoccupation croissante en Afrique, au regard de ses incidences sur les droits de l’Homme, l’environnement et le développement. Dans le contexte du droit international africain des droits de l’Homme, cette responsabilité s’inscrit dans un cadre normatif encore en construction, où se croisent exigences économiques et impératifs de protection des populations. Dès lors, peut-on parler d’un régime de Responsabilité Sociale des Entreprises multinationales extractives en Droit international Africain des D-H ? A travers la méthode analytique, comparative et prospective, l’analyse met en évidence une responsabilité juridiquement ambiguë, révélant d’une part, l’émergence d’une responsabilité à vocation juridique et, d’autre part, la constance d’une responsabilité à portée limitée. The social responsibility of multinational extractive companies is a growing concern in Africa, given its impact on Human rights, the environment, and development. Within the context of African international Human rights law, this responsibility is situated within a still-evolving normative framework where economic demands intersect with the imperatives of protecting populations. Therefore, can we speak of a corporate social responsibility regime extractive multinational in African international human rights law? Through an analytical, comparative, and prospective approach, this analysis highlights a legally ambiguous responsibility, revealing, on the one hand, the emergence of a liability with a legal vocation and, on the other hand, the constancy of limited scope liability.
Keywords: African international law; CSR; Droit international africain; Droits de l’Homme; Entreprises multinationales extractives; Human rights; Legal remedies; Multinational extractive companies; RSE; Recours juridiques; Responsabilité sociale; Social responsibility

Les préoccupations environnementales en droit OHADA des sociétés commerciales - Amougou, Max Aristide (Revue Internationale de Droit et Science Politique, 2025)
De plus en plus, à travers le monde, il est demandé et attendu des entreprises d’aller au-delà de la seule finalité économique et financière au profit des associés et intégrer, entre autres, des considérations environnementales dans leurs décisions. Cette dynamique, est certes lente et timide, mais en construction dans le droit OHADA des sociétés commerciales. Ce droit reçoit implicitement les préoccupations environnementales. Il n’est donc pas totalement indifférent face à l’impérieuse nécessité de protection et de restauration de la nature. Or, l’environnement se vend et fait vendre. Il pourrait alors constituer un facteur de renforcement de l’attractivité du droit OHADA dans son ensemble et faire des sociétés commerciales des entités philanthropiques. L’intégration explicite des préoccupations environnementales dans le droit OHADA des sociétés serait alors requise. Elle accroitrait autant la compétitivité que la crédibilité des entreprises africaines au plan national et international. Increasingly, around the world, companies are being asked and expected to go beyond purely economic and financial objectives for the benefit of their shareholders and to integrate environmental considerations into their decision-making. This dynamic, while admittedly slow and tentative, is taking shape within OHADA business law. This law implicitly acknowledges environmental concerns. It is therefore not entirely indifferent to the pressing need to protect and restore nature. The environment is a marketable commodity and a driver of sales. It could thus become a factor in strengthening the attractiveness of OHADA law as a whole and transform businesses into philanthropic entities. The explicit integration of environmental concerns into OHADA business law would therefore be necessary. This would enhance both the competitiveness and the credibility of African companies at the national and international levels.
Keywords: Business law; CSR; Droit des sociétés commerciales; Environment; Environmental concerns; Environnement; Préoccupations environnementales; RSE

Responsabilité sociale en tant que vecteur de durabilité au sein des coopératives rurales au Bénin - Nakou, Zinsou Daniel; Simen Nana, Serge Francis (L'entreprise, 2025)
Cette recherche vise à élaborer un modèle pour encourager la durabilité chez les agriculteurs en intégrant la responsabilité sociale au sein des coopératives rurales au Bénin. Une méthodologie quantitative, exploratoire et confirmatoire, a été utilisée pour analyser des données recueillies auprès de 358 membres de sept coopératives. Les résultats montrent que la dépendance des coopératives envers le gouvernement est un facteur déterminant pour adopter un comportement socialement responsable. De plus, un manque de pression gouvernementale peut constituer un obstacle à leur engagement dans des programmes de responsabilité sociale. Cet article souligne l'importance de la confiance à long terme et de la coopération entre les coopératives rurales et les agriculteurs pour intégrer la responsabilité sociale dans ces structures. Pour que cette collaboration soit efficace, il est crucial que les besoins des agriculteurs soient au cœur des stratégies des coopératives rurales. Le modèle proposé met en avant la nécessité d'une co-création de valeur entre les acteurs clés, notamment le gouvernement, les coopératives rurales et les agriculteurs, qui doivent unir leurs ressources pour renforcer la responsabilité sociale et construire un avenir durable. This research aims to develop a model to encourage sustainability among farmers by integrating social responsibility within rural cooperatives in Benin. A quantitative, exploratory, and confirmatory methodology was used to analyze data collected from 358 members of seven cooperatives. The results show that the cooperatives' dependence on the government is a determining factor in adopting socially responsible behavior. Furthermore, a lack of government pressure can be an obstacle to their commitment to social responsibility programs. This article highlights the importance of long-term trust and cooperation between rural cooperatives and farmers to integrate social responsibility into these structures. For this collaboration to be effective, it is crucial that the needs of farmers are at the heart of the strategies of rural cooperatives. The proposed model emphasizes the necessity of co-creating value among key stakeholders, including the government, rural cooperatives, and farmers, who must unite their resources to strengthen social responsibility and build a sustainable future.
Keywords: Agriculteurs; Bénin; Coopératives rurales; Durabilité; Responsabilité sociale

L'environnement dans le traité révisé de la CEEAC : une prise en compte mitigée - Meli Fotie, Anthony (International Multilingual Journal of Science and Technology, 2025)
Née à une époque où la protection de l’environnement constituait un leitmotiv sur la scène internationale, il a fallu plus de trois décennies à la CEEAC pour inscrire expressément cette protection dans son texte fondamental notamment son Traité révisé. Nonobstant cet exploit, des manquements sont observables. D’une part, le Traité considère la protection de l’environnement comme un moyen de l’intégration économique et non comme un objectif à part entière de la communauté. D’autre part, l’environnement est appréhendé de manière sectorielle dans le Traité pourtant, la tendance doit être la globalisation de l’environnement par l’inclusion de celui-ci dans tous les politiques sociaux économiques de la communauté tel que se revendique aujourd’hui le développement durable. A l’épreuve, la CEEAC se doit dans son Traité de rendre à l’environnement toute l’attention et l’importance qui lui sont reconnues aujourd’hui. Born at a time when environmental protection was a leitmotif on the international scene, it took more than three decades dor ECCAS to expressly include this protection in its fundamental text, particularly its Revised Treaty. Notwithstanding this feat, shortcomings are observable. On the one hand, the Treaty considers environment protection as a means of economic integration and not as a separate objective of the community. On the other hand, the environment is understood in a sectoral manner in the Treaty, however, the trend most most be the globalization of the environment through the inclusion of it in all, the social and economic policies of the community such as sustainable development is now being promoted. Under the test, the ECCAS must in its Treaty give to the environment all the attention and importance that is recognized for it today.
Keywords: CEEAC; ECCAS; Environment (protection); Environnement (protection); Revised Treaty; Traité révisé

La responsabilité sociétale dans l’ancrage territorial des entreprises du secteur agro-industriel : quel enjeu pour le développement durable au Cameroun ? - Tongue, Thomas Yves (International Multilingual Journal of Science and Technology, 2025)
L’État Camerounais désireux d’attirer des investissements agro-industriels directs se montre parfois complaisant au détriment de la maitrise des impacts locaux de ces entreprises sur l’environnement. Situation qui est permanemment source de conflit avec les communautés locales qui aspirent à protéger leur espace ressource. Dans un contexte de contestations sociales, les entreprises sont de plus en plus interpellées sur leur engagement à la responsabilité sociétale et leur redevabilité environnementale envers leur territoire d’action. Paradoxalement, alors que le Cameroun a adhéré aux idéaux de développement durable, un foisonnement d’initiatives et d’expérimentations faites sur le terrain mettent en exergues plusieurs insuffisances d’une responsabilité sociétale hybride, intuitive qui ne permet pas véritablement à ces entreprises de contribuer au développement durable de leur localité d’implantation et de satisfaire aux attentes des populations locales. Cette réflexion prendra appui sur l’approche des parties prenantes de la responsabilité sociétale des entreprises afin d’en proposer un modèle co-construit adapté à la préservation des intérêts écologiques dans l’ancrage local des entreprises du secteur agro-industriel au Cameroun.
Keywords: CSR; Développement durable; Parties prenantes; RSE; Responsabilité sociétale des entreprises; Social responsibility; Stakeholder; Sustainable development

RSE au Congo: Sortie de l’impasse des réformes imposées en temps de guerres? Vers une politique de responsabilité sociétale de l’entreprise - Ntamwenge, Corneille (International Journal of Innovation and Applied Studies, 2025)
L’étude ne porte ni sur les actes et pratiques de dépossession totale, ni sur les pernicieuses dégradations sociétales identifiées. Elle se penche plutôt sur la problématique de la RSE au Congo, examinant l’évolution de la mise en œuvre des notions de responsabilité sociétale et de codes d’éthique dans les entreprises opérant sur le territoire congolais. La finalité de l’étude comporte trois visées solidaires. La première concerne la conception et la définition de la RSE au Congo, alors que la deuxième, l’existence potentielle d’une politique de RSE pour toutes les entreprises du Congo. Les résultats recueillis à ce niveau impliquent directement la question suivante, troisième visée de l’étude. Comment procéder pour concevoir et instituer une politique pertinente de responsabilité sociétale de l’entreprise au Congo ? Le traitement de cette question a fait ressortir le rôle majeur de la législation et de l’éthique des affaires (EA) dans la politique de RSE au XXIe siècle. L’étude se présente ainsi comme un appel pressant à la conception d’une politique de RSE pour toutes les entreprises actives sur le territoire congolais. Les réflexions et analyses de cette étude sont réparties en six sections: (1) introduction, (2) cadre juridique de la RSE au Congo, (3) expérience congolaise de la RSE, (4) définition de la RSE, (5) histoire de l’EA et de la RSE et (6) remarques conclusives. L’apport de l’éthique des affaires a éclairé l’étude sur trois thèmes, à savoir la RSE, l’institutionnalisation de l’éthique et la mise en œuvre des politiques de RSE. The study does not concern the acts and practices of full dispossession, nor pernicious societal degradations identified. It rather focusses on the issue of CSR in the Congo, examining evolution of implementating notions of societal responsibility and codes of ethics in the enterprises that operate on Congolese territory. Its purpose has three interlinked aims. The first one concerns the conception and definition of CSR in the Congo, while the second, the potential existence of a CSR policy for all Congolese companies. Results collected at this level straightly imply following question, the third aim of the study. How to proceed in designing and establishing relevant corporate societal responsibility policy in the Congo ? The treatment of this issue has highlighted the major function of legislation and business ethics (BE) in CSR policy in the 21st Century. The study thus presents itself as a pressing call for designing a CSR policy for all active enterprises on the Congolese territory. The reflections and analyses of this study are divided into six sections: (1) introduction, (2) legal framework for CSR in the Congo, (3) Congolese experience of CSR, (4) CSR definition, (5) history of BE and CSR, and (6) conclusive remarks. The contribution of business ethics has shed light on the study upon three themes: CSR, institutionalization of ethics, and implementation of CSR policies.
Keywords: CSR; Développement durable; Industrie extractive; Intégrité morale; RSE; Responsabilité sociale de l'entreprise; Régulation non-obligatoire; Éthique des affaires

L’Emergence du concept de la responsabilité sociétale des entreprises en Afrique - Djerma, Ousmane Bazoumana; Sangaré, Sékou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
La responsabilité sociétale des entreprises également appelée responsabilité sociale des entreprises est définie comme la responsabilité des entreprises vis-à-vis des effets qu’elles exercent sur la société. Toutes les entreprises peuvent mettre en œuvre une démarche RSE, et ce qu’elle que soit leur taille, leur forme juridique ou leur secteur d’activité. La responsabilité sociétale permet de conjuguer performance économique, performance sociale et performance environnementale. C’est une démarche accessible à toutes les entreprises. L’entreprise qui déploie une démarche de RSE va donc chercher à développer des pratiques plus éthiques et plus durables dans son mode de fonctionnement de façon à contribuer aux enjeux de développement durable. La RSE est source de nombreux bénéfices pour l’entreprise. Elle permet d’abord de mettre en place une vision stratégique partagée et constitue un vecteur d’engagement et de fidélisation des collaborateurs. Elle a également un outil pour se différencier commercialement, améliorer son image et sa réputation réaliser des gains de productivité et gagner en compétitivité.
Keywords: Afrique; Concept; Emergence; Entreprise; RSE; Responsabilité sociale de l'entreprise

Corporate social responsibility performance of property-development firms in Nigerian south-western urban cities - Oyesomo, Oyewole; Oyedeji, Oyewale; Saheed, Omobolaji; Anifowose, Titilayo (Acta Structilia, 2024)
Previous studies on corporate social responsibility (CSR) in the construction and property-development domain have mainly focused on countries in the Global North with very few studies in the Global South. These prior studies have defined the pyramid elements (economic, legal, ethical, and philanthropic) that make up overall CSR, but none of them have assessed how well corporations performed in relation to each pyramid element, particularly in the property-development industry. Consequently, reflecting on the limited CSR studies in the Global South, this study examines the performance of property-development companies regarding the CSR pyramid elements. The study also assesses the barriers and strategic drivers of CSR among property-development companies. The study employed a descriptive survey research, and questionnaires were administered to 43 property-development companies. Descriptive data analysis was done to rank the relative importance of items from the questionnaire. Results showed that, although companies performed ‘well’ in their legal CSR, and ‘average’ in their economic and ethical CSR, companies performed ‘poorly’ in the area of philanthropic CSR. Lack of support by top management, corruption/lack of transparency, lack of knowledge and awareness by professionals, and lack of regulatory framework were identified as significant barriers to CSR implementation among property-development companies. Vision of founders/support by top management, regulatory framework, stakeholder activism, and good relationship-building are potential key strategic drivers of CSR implementation programmes among property-development companies. Given the findings, it is recommended that property-development companies should integrate CSR principles into their vision and mission statement and consider it to be a business function. This can be done by mitigating the barriers identified through the adoption of strategic drivers as postulated by this study.
Keywords: CSR; RSE

Intégration de la RSE en droit OHADA au travers des codes de gouvernement d’entreprise : pour un changement de paradigme - Byaombe Malumalu, Christian; Nzohabonayo, Anaclet (Revue africaine de droit des affaires, 2024)
La RSE peut s'immiscer en droit des sociétés OHADA au travers des codes de gouvernement, pourvu qu'ils adoptent un changement de paradigme ou de la vision dominante limitée à l'organisation des relations entre les actionnaires et les dirigeants sociaux. Or, pour intégrer les enjeux de la RSE, ces codes doivent élargir leur champ aux différentes parties prenantes à la vie de l'entreprise, notamment des salariés, clients, fournisseurs, créanciers, populations locales et l'État. Un tel changement de paradigme peut se fonder sur la conception mixte de l'intérêt social et la récente consécration du reporting extrafinancier dans l'espace OHADA. Ceci implique par ailleurs que les organisations représentatives des entreprises fassent participer les parties prenantes, en amont, au processus d'adoption et en aval, au contrôle d'application de codes de gouvernement d'entreprise à travers, par exemple, un comité RSE ou ESG.
Keywords: CSR; Gouvernement d'entreprise; RSE

The Extent of Social Responsibility among Libyan and Palestinian Telecom Companies in Mitigating the Effects of the COVID-19 Pandemic - Rashwan, Abdelrahman; Amarif, Suad (Jordan Journal of Applied Science-Humanities Series, 2024)
This study primarily aims to identify the social responsibility of Libyan and Palestinian telecommunications companies and their contributions to addressing the negative effects resulting from COVID-19. The study focuses on the companies’ efforts to alleviate the burden on the state and citizens, exploring the most significant social contributions made by these companies in response to the pandemic. To answer the research questions and test the hypotheses, the researchers employed a descriptive and analytical approach. After obtaining the necessary data, a validated and evaluated questionnaire was distributed to a sample of 53 individuals, including financial managers, internal auditors, financial analysts, and accountants working in Libyan and Palestinian telecommunications companies. The results of the study indicated that Libyan telecom companies did not contribute significantly to mitigating the negative effects of COVID-19 by activating their social responsibility roles. This conclusion is supported by the respondents' answers, which reflected a moderate degree of contribution, with a mean value of 3.08 and a relative weight of 61.69%, along with a standard deviation of 0.85 and a significance level (Sig) of 0.686. Similarly, Palestinian telecom companies also did not significantly contribute to mitigating the negative effects of the COVID-19 pandemic through their social responsibility roles. Respondents’ answers indicated a moderate level of contribution, with a mean value of 3.24, a relative weight of 64.85%, a standard deviation of 0.849, and a significance level (Sig) of 0.256. The study recommends that Libyan and Palestinian telecommunications companies should enhance their social roles in mitigating the negative effects of the COVID-19 pandemic by actively implementing social responsibility initiatives.
Keywords: COVID-19 Pandemic; CSR; Corporate Communications; Corporate Social Responsibility; Libya; Telecom Company

Corporate Social Responsibility and Green Marketing Adoption in Nigeria: A Panoramic View - Nkwede, Maria-Friday; Ogbulie, Angela (African Journal of Politics and Administrative Studies, 2023)
Corporate social responsibility (CSR) and green marketing adoption is a twin trend that is fast becoming a global tendency amongst world economies, irrespective of socio-economic outlook. This paper pedagogically links the two concepts in the Nigeria business climes and explores, through a panoramic view the rate of adoption of CSR and green marketing in Nigeria. This study adopted an exploratory research design vis-à-vis a qualitative research approach. Based on the findings, this paper posits that corporate social responsibility in the Nigerian context is highly “localized” to reflect realities in the Nigerian socio-cultural space. However, green marketing adoption is near impossible for the average Nigerian organization; this is due in part to the enormous funds necessary for implementation of green marketing strategies in their businesses. This study therefore recommends the setting up of trust fund for companies (especially, small scale business) by government; this would give the companies the opportunity to fully develop and adopt green marketing strategy
Keywords: CSR; Corporate Social Responsibility; Customers; Green marketing adoption; Nigeria; RSE

Propos conclusifs. Durabilité et régulation de l'entreprise sociétaire : La directive sur la publication d’informations en matière de durabilité, au cœur d’un renouvellement paradigmatique - Trébulle, François Guy (Revue Juridique de la Sorbonne, 2023)

Accounting Choices During COVID 19 Pandemic: Does Corporate Strategy and Corporate Social Responsibility Matter? - T. Hassan, N. (Information Sciences Letters, 2023)
This study aims to understand the accounting effects of the Corona pandemic in more depth and clarity, where the study explores the accounting choices during the pandemic period and the impact of the firm's strategic orientation and its social responsibility performance on those choices. Using data from non-financial Saudi companies, the accounting choices divided into aggressive accounting strategy and conservative accounting strategy, and regression models used to examine the study hypotheses. The results of the study provide a clearer and in-depth vision about the nature of accounting practices during the pandemic and indicated that business strategy affects accounting choices, while corporate social responsibility does not affect. The results can imply useful information for the market regulators that help them in controlling and stabilizing the market, as well as for professional accounting organizations to help them issue guidelines for accounting work during crises.
Keywords: Accounting choices; CSR; Corporate Social Responsibility; Corporate strategy; Covid-19 pandemic; Saudi companies

Corporate human rights obligations of investors in recent investment agreements: The progressive hardening process of CSR clauses - Francis Maïnkade, Belengar (Heliyon, 2023)
Since the earlier indirect Corporate Social Responsibility (CSR) provisions failed to hold investors responsible for human rights abuses, the recent hardening process of direct CSR clauses has resulted in incorporating CSR clauses under sections or chapters entitled “investors obligations” and tying CSR obligations to binding human rights and environmental prohibitions, as well as to human rights obligations established by the host state's legislation. This paper provides a non-exhaustive analysis of recent developments in treaty practice based on research primarily sourced from investment agreements concluded between 2012 and 2021, doctrinal input, and normative analysis. As shown in this paper the hardening process has not yet been completed, and reformations are necessary. Specifically, new investment agreements should enshrine investor human rights obligations as legally binding obligations, consider violations of these CSR obligations as part of investment disputes and provide direct remedies to victims. This study contributes to the literature on the international responsibility of TNCs with regard to human rights by examining the process of hardening up the CSR obligations within investment agreements as an approach that could lead to effective human rights protection.
Keywords: Corporate Social Responsibility; Corporate human rights responsibility; Hardening of corporate social responsibility clauses; International responsibility of transnational companies; Investors' human rights obligations

Challenges of CSR in Sub-Saharan Africa: clarifying the gaps between the regulations and human rights issues - Ndong Ntoutoume, Achille Gildas (International Journal of Corporate Social Responsibility, 2023)
This paper discusses the practice of Corporate Social Responsibility (CSR) and its challenges in Sub-Saharan Africa. The main purpose is to highlight and clarify the gaps between CSR regulations and human rights abuses caused by business organizations.
Keywords: Business and human rights; CSR; Stakeholders; Sub-Saharan Africa

African Economic Integration Initiatives and the Challenge of Responsible Business Conducts: Analysis of Corporate Social Responsibility Provisions in African Regional Trade and Investment Agreements - Azapmo, Jean Bertrand (Revue Interventions économiques, 2023)
Left alone, economic integration initiatives, which aim to promote growth through investment and trade liberalization, do not automatically generate win-win outcomes for all stakeholders, or lead to the inclusive economic growth and sustainable development of participating countries. This situation which is due among others to possible market failures and externalities of corporations’ activities, has increasingly become a matter of concern with the numerous corruption scandals; human rights violations and environmental degradation involving corporations observed in a recent past. How therefore to continue promoting economic integration while ensuring socially responsible conducts from businesses in societies where they operate? One approach that has recently gained traction is the institutionalization of corporate social responsibility (CSR) clauses in trade and investment agreements. This paper analyses 10 African regional trade and investment agreements concluded between 2000 and 2020 to determine the extent to which they converge with this trend and the approach adopted in regulating CSR. The research complements the literature on the nexus between international law and CSR in the African context. Laissées à elles-mêmes, les initiatives d'intégration économique, qui visent à promouvoir la croissance par la libéralisation commerciale et économique, ne génèrent pas automatiquement des résultats gagnant-gagnant pour toutes les parties prenantes, ou ne conduisent pas à la croissance économique inclusive et au développement durable des pays participants. Cette situation, qui est due entre autres à d’éventuelles défaillances du marché et à des externalités des activités des entreprises, est devenue de plus en plus préoccupante avec les nombreux scandales de corruption, de violation des droits de l’homme et de dégradation de l’environnement impliquant des entreprises. Comment donc continuer à promouvoir l'intégration économique tout en garantissant des comportements socialement responsables des entreprises dans les sociétés où elles opèrent ? Une approche qui a récemment gagné du terrain est l'institutionnalisation des clauses de responsabilité sociale des entreprises (RSE) dans les accords de commerce et d'investissement. Cet article analyse 10 accords régionaux africains de commerce et d'investissement conclus entre 2000 et 2020 pour déterminer dans quelle mesure ils convergent avec cette tendance à l’institutionnalisation des clauses sur la RSE, et l'approche adoptée dans la réglementation de la RSE. La recherche complète la littérature sur le lien entre le droit international et la RSE dans le contexte africain.
Keywords: Accords régionaux d'investissement; Accords régionaux de commerce; AfCFTA; CEDEAO; Corporate Social Responsibility; ECOWAS and SADC; Economic integration; Intégration économique; SADC; ZLECAf; regional trade and investment agreements; responsabilité sociale des entreprises

Vers un modèle de RSE issu du discours des entrepreneurs en Afrique subsaharienne : résultats d’une étude dans le contexte camerounais - Biwole Fouda, Jean; Kamga, Charles (Management international, 2023)
L’objet de cet article est de révéler un modèle de RSE issu du discours des entrepreneurs en contexte africain. Les concepts de justification et de légitimation, associés à l’approche du mécanisme conciliateur sont mobilisés pour analyser le contenu des entretiens menés auprès de dix entrepreneurs de TPE implantées au Cameroun. Il apparait que, dans ce contexte, l’entrepreneur perçoit sa responsabilité en se situant à la fois dans des mondes domestique, marchand et spirituel. Le modèle de la RSE qui émerge est tridimensionnel. Il correspond à une agrégation des responsabilités généalogique, géo-économique et spirituelle, chacune étant ancrée respectivement dans un des mondes suscités. Les discours et pratiques de RSE à promouvoir sur ce continent pourraient s’en inspirer.
Keywords: Afrique subsaharienne; CSR; Cameroon; Cameroun; Camerún; Conciliator mechanism; Justificación; Justification; Legitimación; Legitimation; Légitimation; Mecanismo conciliatorio; Mécanisme conciliateur; RRSE; RSE; Sub-Saharan Africa; TPE (Très Petites Entreprises); Very Small and Small Enterprises; África subsahariana

La Responsabilité sociale des entreprises dans l’aménagement des rapports entre l’Etat d’accueil et l’investisseur étranger - Koultchoumi Ahmed, Hadja (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
Qu’il soit de substance, issu des textes internationaux, le principe de précaution ne définit aucune règle d’incrimination précise en droit interne ; ce qui contraste avec le principe de légalité qui dispose qu’on ne peut être condamné pénalement qu’en vertu d’un texte pénal précis et clair. Ce qui rend, en principe, le principe de précaution inopérant sur le terrain de la responsabilité pénale. Cependant, le juge peut, dans une certaine mesure, insinuer le principe de précaution dans certaines incriminations afin d’accorder une meilleure protection aux victimes d’accidents, tel que celui de la médecine, suite à l’incertitude que contiennent les innovations de la science et de la technologie.
Keywords: CSR; Dommage; Incertitude; Incrimination; Irréversible; Mesure de précaution; Principe de légalité; Principe de précaution; Prévention; RSE; Risque

La publication des informations sociétales suivant les lois comptables revisées OHADA - Guimezap Épse Choukem, Claire (Revue Française d'Economie et de Gestion, 2021)
Dans un contexte marqué par le développement durable, le législateur OHADA n’a eu de cesse d’être accablé de toutes parts pour son statisme vis-à-vis de la montée des problématiques sociétales. Au lendemain des reformes du système comptable OHADA, les problématiques sociétales ont une fois de plus raté le rendez-vous de la normalisation. Toutefois, de nombreuses entreprises continuent à publier leurs informations sociétales parallèlement à leur communication financière. A cet effet, le problème que soulève cet article est celui de la compréhension des modes de production et de diffusion des informations extra-financières en l’absence d’une réglementation en la matière. Une étude empirique de nature descriptive est menée auprès d’un échantillon de 120 entreprises diffusant leurs informations sociétales au sein de l’espace OHADA. Il en ressort que le site internet et l’implication dans le développement de la communauté locale sont apparue respectivement comme support et thème de diffusion les plus utilisés dans l’espace OHADA en matière de reporting sociétal sous la pression de certaines parties prenantes notamment les associations consuméristes, les départements ministériels en charge de l’environnement, du travail et de la sécurité sociale. In a context marked by a widespread awareness of the needs of sustainable development, the OHADA legislator has been constantly burdened on all sides for its statism to the rise of societal problems. However, After the reform of the OHADA system, sustainability problems once more did not met up with the appointment of normalization. However, several enterprises continue to publish their societal information in parallel with their financial communication. As such, the problem raised by this article is that of understanding the mode of production and disclosure of non-financial information in the absence of a regulatory framework. A descriptive empirical analysis is carried out with a sample of 120 enterprises which propagate their societal information in the OHADA zone. It reveals that internet websites and implication in the development of the local community are respectively the medium and theme of the most used disclosures in the OHADA zone with regards to sustainability reporting under the pressure of some stakeholders especially consumer associations, ministerial departments in charge of the environment labor and social security.
Keywords: Accounting law; CSR; Corporate Social Responsibility; Droit comptable; Information sociétale; Parties-prenantes; RSE; Responsabilité Sociétale de l'Entreprise; Stakeholders

Corporate social responsibility and management of oil related conflict in Host Communities of Niger Delta Region, Nigeria - Gbali, Kenneth Chisom; Weli, Vincent Ezikornwor; Mmom, Prince Chinedu (World Journal of Advanced Research and Reviews, 2021)
The study sought to examine the Corporate Social (CSR) and management of oil related conflicts in Host Communities of the Southern States. Corporate Social Responsibility is the commitment of businesses to contribute to sustainable economic development by working with employees, the local community and the society at large to improve their lives in ways that are good for business and for development. The study was guided by three research objectives, three research questions and three hypotheses. The design adopted for this study is exploratory and descriptive research design and was conducted in Bayelsa, Delta and Rivers State in Nigeria. The population of this study comprised of 15,245,247 residents in Bayelsa, Delta and Rivers State in Nigeria. The instrument for data collection was a set of structured questionnaire. Data derived from the field were analyzed using the Statistical Package for Social Sciences (SPSS) version 23.0. And statistical tools such as mean and standard deviation were used to respond to the research questions, while inferential statistical tool of independent sample T-test was used to test the hypotheses at 0.05 level of significance. Findings from the study showed that there is a significant difference in the mean ratings of male and female respondents on the level of relationship between IOC’s and hosts Communities in Niger Delta Region, Nigeria ((P=0.738>0.05), df (400) =. -0.49273, p=0.738); there is a significant difference in the mean ratings of male and female respondents on the on CSR programs carried out by IOCs in hosts Communities in Southern Nigeria (P=.117>0.05), df (400) = -401.618, p=.117); further findings showed that there is a significant difference in the mean ratings of male and female respondents on the Factors causing conflict between oil companies and host communities in Southern, Nigeria (P=0.775>0.05), df (400) =382.256 p=0.775). Based on the findings of the study, it was recommended that host communities should be integrated into the planning process, a paradigm shift from planning for to planning with the host Communities, amongst others.
Keywords: CSR; Corporate Social Responsibility; Host communities; Oil Related Conflict; Oil companies; Southern Nigeria

Relationship between corporate social responsibility practice and its effects on the botton-line - Tandoh, Isaac; Aovare, Ayishetu (International Journal of Innovation and Scientific Research, 2020)
The study comparatively evaluates the relationship between Corporate Social Responsibility and Profitability in the fuel and gas sectors in Ghana. The descriptive survey design and quantitative methods was adopted to find a relationship between innovations in strategic stakeholder engagement with corporate profitability or bottom-line, with the mediating role of strategic stakeholder engagement leading to a firm’s bottom-line. An analysis of strategic stakeholder engagement and bottom-line of selected fuel and gas companies in the Kumasi Metropolitan, Asokore Mampong, Oforikrom and Ejisu Municipalities was provided.A five point closed ended Likert Scale self-administrable structured questionnaire and researcher guide to aid participants answer relevant questions was used to confirm that innovations in strategic stakeholder engagement fueled increases in corporate bottom-line of selected companies. The four major steps of analysing data collected from Atkinson’s (2002) categories of quantitative data analysis was used, following which the primary data/information gathered and coded was analysed using the Statistical Package for Social Sciences to guarantee validity and reliability of the various investigations conducted. The hierarchical multiple regression of the Baron and Kenny’s (1986) procedure was also adopted to analyse for study the mediating effect of innovation on the relationship between strategic stakeholder engagement and corporate bottom-line.The study opines the involvement of key stakeholder participation in the siting and general operations of fuel and gas companies given the divergent viewpoints of operators and stakeholders (O’Riordan, 2017). A discovery of a statistically significant positive influence of perceptions of CSR towards customers on an organization’s image in general intensifies the suggestion that mangers of fuel and gas sectors take special interest in innovative ways of engaging strategic stakeholders due to its influence and ripple mediating effect on corporate bottom-line to improve the performance of the business or induces increases in profit.
Keywords: Brand; Corporate Social Responsibility; Employees; Image; Perception; Strategic Stakeholder

The Trajectory of Illicit Waste Trade in Africa: Implications for Human Rights and Sustainable Development - Umenze, Nnamdi Stanislaus (Journal of Law, Society and Development, 2020)
As globalisation intensifies, the environmental burden of economic development is being shifted to poor countries. This development manifests in waste trade involving the transboundary shipment of toxic waste from developed to developing countries. This article evaluates the strategies with which waste trade is being perpetuated to the detriment of sustainable development and human rights values in Sub-Sahara Africa. It argues that capitalism has influenced massive generation and commodification of waste, especially in industrialised countries. It has also established that globalisation has made the transboundary shipment of waste easy. Moreover, foreign investments in the waste industry in developing countries appear to be a means by developed countries to perpetuate waste shipment to developing countries, which helps waste traders to avoid stringent regulations and high costs of waste management in developed countries. Therefore, such investments in developing countries should not always be viewed as a breakthrough in attracting foreign investments. The findings made include that despite the existence of the Basel and Bamako Conventions at global and regional levels, respectively, waste trade has continued in different forms in Africa, where waste merchants exploit the low-cost facilities, cheap labour and weak regulatory frameworks. The trend includes the reckless dumping of hazardous industrial waste, electronic waste as well as ostensible investment in “dirty industries” in some African countries. It concludes by urging the states to individually establish robust mechanisms that protect the environment and enforce environmental rights. These measures will help complement the collective efforts they have made in multilateral and regional agreements.
Keywords: Africa; electronic waste; globalisation; human rights; sustainable development; toxic waste trade

Corporate Social and Environmental Reporting in OHADA Context: Evidence from Companies Listed on the Douala Stock Exchange - Nganthou, Alexis; Boukar, Hamadou; Djeugou, Gaelle (Research Journal of Finance and Accounting, 2019)
This research questions the capacity of the OHADA accounting system to report on the societal commitment of companies. To carry out such a study, we are interested in the companies of the Douala Stock Exchange, which permanently publish green operations. The analysis was done at two levels: the first level of analysis highlighted the categories of green operations reported by the companies of our sample. The second level of analysis consisted in analysing the financial statements produced by these companies, in order to see in which accounts green transactions are recorded. The analysis reveals that, apart from some additional clarifications to be made in the appendices, the financial statements produced according to OHADA do not specifically highlight green information.
OpenAlex: https://openalex.org/W2998516176
Keywords: Carry (investment); Green operations; Publication; Sample (material); Societal commitment; Stock (firearms)

Firmes TIC et responsabilité sociétale des entreprises en Afrique, cas du congo - Bokilo Lossayi, Julien (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2019)
L’analyse des enjeux de la responsabilité sociétale des entreprises (RSE) des firmes TIC en Afrique se fait en tenant compte du degré de structuration de chaque Etat (démocratique ou non) qui en influence la forme et détermine le type de RSE. Partant du postulat selon lequel la RSE peut être le palliatif d’un Etat défaillant, l’objectif de cette étude est d’analyser l’impact sur les populations pauvres et vulnérables des politiques sociétales des firmes. L’enjeu scientifique de cette analyse, à partir d’études de cas africains, et du Congo en particulier, est aussi de réfléchir sur l’ambivalence de l’impact des politiques sociales des firmes TIC en Afrique, afin de montrer l’opportunité qu’offre le développement exponentiel des nouvelles technologies de la téléphonie dans la mise en oeuvre des politiques sociales dans ces pays. Aussi, en filigrane, ce travail questionne la prise en compte, dans les politiques relatives à la RSE de ces firmes, des conséquences du processus de production des consommables et accessoires TIC sur les populations, en l’occurrence les jeunes enfants travaillant dans les mines. Analysis of the issues of the corporate social responsibility (CSR) of the ICTs in Africa companies is done taking into account the degree of structuring of each State (Democratic or not) which influence the form and determines the type of CSR. Starting from the premise that CSR can be the palliative of a failed State, the objective of this study is to analyze the impact on poor and vulnerable people of firm’s societal policies. The scientific issue of this analysis, based on studies of African cases, and the Congo in particular, is also to reflect on the ambivalence of the impact of social policies of the ICTs firms in Africa, in order to show the opportunity that offers exponential development of NICTs in implementation of social policies in these countries. Also, implicitly, this work questions taking into account, in policies on CSR of these firms, of the consequences of the process of production of consumables and accessories ICT on populations, in this case young children working in the mines.
Keywords: CSR; Congo; Corporate Social Responsibility; ICT; RSE; Responsabilité sociale des entreprises; Responsabilité sociétale; TIC

Cadres théoriques d’inspiration de recherches en contrôle de gestion et pilotage de la performance organisationnelle à l’ère de la responsabilité sociétale des entreprises (RSE) - Oubba, Omar; Akrich, Said (International Review of Economics, Management and Law Research, 2018)
L’objectif du présent article est d’essayer, à travers une étude théorique, de mettre en évidence les principaux cadres théoriques d’inspiration des recherches en contrôle de gestion et le pilotage de la performance organisationnelle à l’ère du contexte actuel, caractérisé par une grande tendance des entreprises vers l’adoption et l’intégration de la RSE. Il ressort de la littérature une diversité d’approches et des courants de contrôle de la RSE. Ainsi, les résultats escomptés stipulent qu’un grand nombre de recherches en contrôle de gestion et le pilotage de la performance organisationnelle à l’ère de la RSE, se réfère à la théorie des parties prenantes, la théorie de contingence, le cadre théorique de Simons (1990, 1991, 1994, 1995) et la théorie néo-institutionnelle. Ces théories constituent la référence fondamentale pour comprendre les déterminants du dynamisme, les évolutions voire les reconfigurations des systèmes de contrôle de gestion. Selon la littérature, les apports de la théorie des parties prenantes et ceux de la contingence permettent d’expliquer les tendances des entreprises vers la prise en compte des dimensions autres que financières et économiques de la performance. Aussi, la théorie de contingence fournit à l’entreprise une diversité des facteurs sur la base desquels elle peut concevoir les dimensions de sa performance organisationnelle élargie. Ainsi, le cadre théorique de Simons est une référence fondamentale pour comprendre la relation entre les stratégies des entreprises, leurs modes de pilotage et de contrôle, et les dimensions visées de la performance organisationnelle.
Keywords: CSR; Cadre théorique de Simons; Contingency theory; Contrôle de gestion; Management control; Neo-institutional theory; Performance; Pilotage; Piloting; RSE; Simons theoretical framework; Théorie de contingence; Théorie néo-institutionnelle

La responsabilité sociétale des entreprises au Maroc : entre l’engagement effectif et l’investissement marketing - Mounir, Yaser; Moflih, Youssef (International Journal of Innovation and Scientific Research, 2018)
Le concept de responsabilité sociétale des entreprises (RSE) a une histoire longue et variée associée à l'évolution du concept et à la définition de la responsabilité sociétale des entreprises (RSE). Par ailleurs, bien qu'il soit possible de voir les empreintes de la RSE dans le monde, les écrits formels ont été les plus évidents aux États-Unis, où un nombre considérable de publications s'est accumulé. Ce mouvement de la responsabilité sociétale des entreprises a connu naissance dès les années 1950 aux Etats-Unis avant qu’il ne soit apparu en Europe lors des années 1990. En effet à partir de l’apparition de de l’ouvrage « Social Responsibilities of the Businessman (SRB) » de Howard R. Bowen qui est identifié comme le père fondateur de la notion de Responsabilité Sociale de l’entreprise, différentes définitions ont été rédigées par rapport à ce concept, et à ce jour aucune définition ne semble avoir le consentement dans le monde entier pour aboutir à une pensée universelle. Notre objectif à travers ce document est de mettre en évidence l'évolution conceptuel de la responsabilité sociétale des entreprises et nous présentons également les différentes définitions les plus largement utilisées qui sont de caractère exhaustif. The concept of corporate social responsibility (CSR) has a long and varied history associated with the evolution of the concept and the definition of corporate social responsibility (CSR). on the other hand, although it is possible to see CSR fingerprints around the world, formal writings have been most evident in the united states, where a considerable number of publications have accumulated. this movement of corporate social responsibility began in the 1950s in the United States before it appeared in Europe in the 1990s. indeed, from the appearance of the book «Social Responsibilities of the Businessman (SRB) » of Howard R. Bowen who is identified as the founding father of the concept of corporate social responsibility, different definitions have been written in relation to this concept, and to this day no definition seems to have the consent around the world to achieve universal thinking. our objective through this document is to highlight the conceptual evolution of corporate social responsibility and we also present the various most widely used definitions that are exhaustive in nature.
Keywords: Business; CSR; Corporate Social Responsibility; Entreprise; RSE; Responsabilité sociale/sociétale; Society; Société

Assessing the nexus between corporate governance, corporate social responsibility and corporate regulation: the way forward for the OHADA zone - Tambutoh, Dashaco John; Tarh, Bande Gulbert Mbah (International Journal of Advanced Research and Publications, 2018)
Encyclopaedic Corporate Governance (CG) is now a mainstream issue of concern in the business world. Yet, there has been no systematic investigation of CG practices in general, allowing for a distinction between the profit and non-profit organizations. In this regard, this article aims to investigate the nuances in the application of sound governance principles across different types of organizations in general, together with the understanding and applications of Corporate Social Responsibility (CSR) and Corporate Regulation (CR) in the context of the OHADA zone. With CSR envisages as a model of CG that extends the fiduciary duties from fulfilment of responsibilities towards the shareholders of the firm to fulfilment of analogous fiduciary duties towards all the firm?s stakeholders. Thus, after considering the place of CSR in the debate about alternative CG modes, a full-fledged social contract foundation of the multi-stakeholder and multi-fiduciary model is present. The article, therefore, shows that CSR is a social norm that would endogenously emerge from the stakeholders? social contract seen as the first move in an equilibrium selection process that reaches the equilibrium state of a CG institution; and as a global trend involving corporations, states, international organizations and civil society organizations. Besides, the article portrays the trend of CSR in three ways: as a regulatory framework that places new demands on corporations; as a mobilization of corporate actors to assist the development aid of states and; as a management trend. With each of these portraits suggesting certain actors, relations, driving forces and interests as being central. These multiple identities may partially describe the trend?s success, but could equally well describe its contestation, fragility and fluidity. Based on the argument that CSR is not just a fashion but rather the future from another angle, the article explicitly explores the nexus between CSR, CG and CR as appreciated in the OHADA zone. It also presents fresh insights into the applications of CG and CSR principles under the OHADA perspective that has not received systematic attention and consideration in the literature and, thus, provides policy recommendations to mainstream a viable CSR framework in the OHADA zone.
http://www.journalijar.com/
Keywords: Corporate Regulation; Corporate Social Responsibility; Corporate governance; OHADA

Modélisation d’un Indice de Performance de la Responsabilité Sociétale selon la norme ISO 26000 - Fethallah, Widad; Chraibi, Lotfi; Sefiani, Naoufal (International Journal of Innovation and Scientific Research, 2017)
Le présent travail consiste à développer un nouveau modèle relatif à l’évaluation de la performance responsabilité sociétale de l’organisation (RSO) basé sur une approche holistique et interdépendante issue des fondements et principes de la norme ISO 26000. Le modèle d’évaluation proposé génère des indices de mesure RSO, qui aideraient l’organisation à caractériser et évaluer sa performance par rapport aux sept questions centrales, dans le but d’améliorer sa démarche RSO, et ce dans une logique participative avec ses diverses parties prenantes. Inspiré des travaux de G. K. Kanji et P. K. Chopra, nous proposons un modèle d’équations structurelles composé de variables latentes et de variables manifestes. L’avantage du modèle permet de mieux cerner les diverses connections et causalités entre les différentes composantes (les questions centrales). L’implémentation du modèle sur le logiciel XLSTAT fournit des indices de mesure pour chaque variable latente qui peuvent être analysés et interprétés afin de développer les plans d’actions et les aspects à améliorer dans la démarche RSO. The aim of the present work is to develop a new model to assess the Corporate Social Responsibility CSR performance of an organization based on a holistic and interdependent approach as described in the foundations and principles of the ISO 26000 standard. The proposed model generates a new Corporate Social Responsibility (CSR) Index, which help the organization to characterize and assess its performance regarding to the seven core subjects of ISO 26000 standard, with the different stakeholders. Inspired by the work of G. K. Kanji and P. K. Chopra, we propose a model of structural equations composed of latent and manifest variables. The model identifies the various connections between the different components (the core subjects). The implementation on the XLSTAT software provides an index for each latent variable that can be analysed in order to improve the CSR performance.
Keywords: CSR Index; Corporate Social Responsibility; Indice RSO; Latent Variable; Manifest Variable; Modèle d’équations structurel; Partie prenante; Responsabilité sociétale de l’organisation; Stakeholders; Structural Equation Model; Variable Manifeste; Variable latente; XLSTAT Software; logiciel XLSTAT

CSR and financial performance parameters of DBBL: An empirical analysis - Farijul, Islam; Rahman, Mostafizur (International Journal of Innovation and Scientific Research, 2016)
The purpose of the current study is to show the statistical linkage between CSR expenditure of financial service firm mainly DBBL and its financial performance on the basis of some key parameters that attempts to contribute to the existing knowledge of corporate social responsibility initiatives by businesses and its ability to influence their financial performance. Consequently, the main objective is to examine the relationship between CSR and financial performance of the banking sector. For this purpose, various financial drivers are used such as EPS, DPS, NPAT, ROE, EVA ROA, MVA and, ROE and ROI. After getting all the relevant data from secondary sources like annual reports and reports from Bangladesh Bank, statistical tool like multivariate analysis in the form of Bi-variate Regression is used to depict the relationship and the developed hypotheses are tested by using Univariate analysis in the form of one sample t test under parametric test. The major finding of this study demonstrates evidence that there is a statistical significant linkage between CSR and Performance of the sample bank.
Keywords: CSR; DBBL; Financial performance parameters

Corporate Social Responsibility , Oil Exploration and the Niger Delta Question - Obi, Emeka Anthony (Oman Chapter of Arabian Journal of Business and Management Review, 2015)
The intricate relationship between corporate organizations and their environment is one that is supposed to be based on mutual interdependence. This is because the organization depends on the environment for its inputs, while the environment also needs the organization for its sustenance. This therefore calls for a symbiotic relationship between them. It is this realization that gave birth to the concept of Corporate Social Responsibility (CSR). This paper tries to look at the application of the concept as it concerns the oil companies operating in the Niger Delta region of Nigeria within the ambit of the Niger Delta question. The study employs the systems theory as an analytical framework. It tries to situate the concept of CSR within the general neglect by successive governments of this region that sustains the entire Nigerian state. The implication of the above is that a better understanding of the problem of CSR in the Niger Delta region becomes easier when juxtaposed with the attitude of the Nigerian state towards the region over the years. It is the summation of the paper that the oil companies have not been very proactive in this regard and as such have been perceived by their host communities as enemies and exploiters instead of partners. The study concludes by insisting that while the oil companies should be more proactive, the government on her part should step up the tempo in ameliorating the deplorable condition of the golden goose.
Keywords: CSR; Corporate Social Responsibility; RSE; Responsabilité Sociale de l'Entreprise

The primary importance of corporate social responsibility and ethicality in corporation reputation: an empirical study - Walker, Kent; Dyck, Bruno (Business and Society Review, 2014)
We examine three assumptions commonly held in the corporate reputation literature: i) reputation ratings of owners and investors are generally representative of all stakeholders; ii) stakeholders will generally provide a higher reputation rating to firms that emphasize corporate social responsibility versus firms that do not; and iii) profitability is the primary criterion of importance to all stakeholders when rating a firm’s reputation. Using an exploratory in-class exercise our findings suggest that: i) there are significant differences among stakeholder groups in their reputation ratings; ii) firms that emphasize corporate social responsibility are not rated more highly across all stakeholder groups, and iii) for all stakeholder groups, the ethicality criterion explained more of the variance in firms’ reputation ratings than the profitability criterion.
Keywords: CSR; Corporate Reputation; Corporate Social Responsibility; Criteria; Ethics; Profitability; RSE; Stakeholders

Corporate Social Responsibility (CSR) in the OHADA Law - Diawara, Karounga; Lavallée, Sophie (Journal of Business Law and Ethics, 2014)
CSR refers primarily to a framework idea according to which a corporation is encouraged, if not obliged, to go beyond the speculative and economic goals that benefit its members only, in order to integrate, into its decision-making process, other more holistic considerations of an ethical, social and environmental nature for the benefit of all stakeholders. CSR is a key concept that attempts to reconcile economic objectives with social, ethical and environmental considerations, with the particularity of questioning interactions between a corporation and its societal, ethical and ecological environment. This paper has a modest, but not uninteresting, objective. First, it offers an exploratory study that sets out markers for a more exhaustive analysis of the potential for CSR in the field of law in the Ohada zone. Our study is intended to be both theoretical and pragmatic: it asks questions and suggests topics for review from a normative standpoint largely inspired by socio-economic analysis. One of the interesting features of our approach is to consider, comprehensively, a complex notion that reflects several different concerns and is crossed by various conceptual frameworks that must be re-read in an “enlightened” manner, to see how it could potentially be made operational as part of Ohada law. This previously unexplored approach could lead, in time, to the establishment of a transnational committee on CSR in the Ohada zone.
Keywords: CSR; RSE

La responsabilité sociale de l’entreprise (RSE) dans l’espace OHADA : pour une ouverture aux considérations non économiques - Diawara, Karounga; Lavallée, Sophie (Revue internationale de droit économique, 2014)

Exploring the limits of Western Corporate Social Responsibility Theories in Africa - Dartey-Baah, Kwasi; Amponsah-Tawiah, Kwesi (International Journal of Business and Social Science, 2011)
Corporate Social Responsibility (CSR) is about the relationship of organisations with society as a whole, and the need for organisations to align their values with societal expectations. Generally, CSR practice in Africa is thought to be adopted from Western business theories although there is evidence to suggest that Western CSR theories are not totally applicable in Africa. This is due to differences in drivers or causes of CSR in the West and in Africa, as well as cultural and managerial traits in Africa. This paper explores the limits of Western CSR Theories in Africa and argues that improved ethical responsibilities, incorporating good governance should be assigned the highest CSR priority in developing countries. It further adds that increased legislation, change in CSR priorities and the application of indigenous CSR theories such as Ubuntu, African Renaissance and Omuluwabi are means of countering the limits of Western CSR theories in Africa. Keywords: CSR, Western CSR Theory, Africa, Ubuntu, African Renaissance, Omuluwabi
Keywords: Africa; CSR; RSE; Renaissance; Ubuntu; Western CSR Theory